从《上洞八仙传》到《八仙得道传》的人物形象与故事内容演变研究 = Tales and characters portrayal from "Journey to the East" to "The eight immortals enlightenment" - 李瑛瑛 Lee, Yin Yin (2016)
许多人对于八仙的认识大都是通过耳熟能详的“八仙过海，各显神通”故事得知，这里的八仙，指的是明代吴元泰《东游记》，原名《上洞八仙传》中的八仙，即铁拐李、钟离权、吕洞宾、张果老、蓝采和、何仙姑、韩湘子和曹国舅，然而大家对于八仙得道的过程却众说纷纭。许多文献对于八仙在小说中个别的形象、故事的发展缺少系统性的整理工作。因此，笔者将针对八仙在明代吴元泰《东游记》与清代无垢道人《八仙全传》，又名《八仙得道传》中的人物形象与故事内容的演变进行系统性的分析和综合性的整理。Many people 's understanding of the Eight Immortals mostly through the familiar story of the Eight Immortals. In this thesis, the Eight Immortals refers to Tieguai Lee, Zhongli Quan, Lǔ Dongbin, Chang Guolao, Lan Caihe, He Xiangu, Han Xiangzi and Cao Guojiu depicted in the " Journey to the East ", formerly known as " The Eight Immortals Biography" by the author Wuyuan Tai from Ming Dynasty . However, everyone has different opinions for the Eight Immortals enlightenment process. Many documents for the Eight Immortals in the novel individual images development of the story is missing systematic collation. Therefore, I will focus on the Eight Immortals in Wuyuan Tai Ming Dynasty " Journey to the East " and the Wugou Daoren Qing Dynasty "The Eight Immortals Biography " also known as "The Eight Immortals Enlightenment " of the characters and the evolution of the stories to undertake a systematic analysis and comprehensive consolidation.